2017
DOI: 10.1021/acs.inorgchem.7b00646
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Iron-Based Polynuclear Magnetic Superhalogens with Pseudohalogen CN as Ligands

Abstract: To explore stable polynuclear magnetic superhalogens, we perform an unbiased structure search for polynuclear iron-based systems based on pseudohalogen ligand CN using the CALYPSO method in conjunction with density functional theory. The superhalogen properties, magnetic properties, and thermodynamic stabilities of neutral and anionic Fe(CN) and Fe(CN) clusters are investigated. The results show that both of the clusters have superhalogen properties due to their electron affinities (EAs) and that vertical deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…For instance, the superhalogen properties of titanium-related species are very limited . Since a plenty of studies have demonstrated that polynuclear clusters can form superhalogens more effectively, ,,, it is very interesting to see whether the polynuclear clusters of titanium can behave as a new class of superhalogens.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the superhalogen properties of titanium-related species are very limited . Since a plenty of studies have demonstrated that polynuclear clusters can form superhalogens more effectively, ,,, it is very interesting to see whether the polynuclear clusters of titanium can behave as a new class of superhalogens.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of ligands bound to a single central atom cannot be increased beyond certain values (mostly due to destabilizing valence repulsion effects and steric hindrance). Hence, polynuclear superhalogen anions matching the (M n X n×k+1 ) – formula in which an excess electron density is expected to delocalize over n× k +1 electronegative ligands have been extensively studied in recent years ( Alexandrova et al, 2004 ; Anusiewicz and Skurski, 2007 ; Freza and Skurski, 2010 ; Sikorska and Skurski, 2012 ; Wileńska et al, 2014 ; Yin et al, 2014 ; Li et al, 2015a , 2015b , Li et al, 2015 M.-M. ; Czapla and Skurski, 2015 , 2018 ; Díaz-Tinoco and Ortiz, 2016a ; Díaz-Tinoco and Ortiz, 2016b ; Sun et al, 2016b ; Ding et al, 2017 ; Zhao et al, 2017 ; Anusiewicz et al, 2018 ; Cyraniak et al, 2019 ; Shi et al, 2019 ). Even though the polynuclear superhalogens investigated to date contain various central atoms (e.g., Li, Na, Mg, Ca, B, Al, Ge, Sn, P, Ti, Sb, As, V, In, Ta, Fe, Au, Pt), the systems utilizing nitrogen central atoms have not been proposed thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Such kind of clusters are regarded as superatoms. , They usually have high thermodynamic stability, providing an entirely new “third dimension” to the traditional periodic table of elements. , Compared with single atoms, one advantage of superatoms is that their physical and chemical properties can be easily controlled by varying their size and composition, which enables the bottom-up synthesis of materials with novel nanostructures and tailored properties. , Superhalogen is a typical class of superatom whose electron affinity (EA) is even larger than that of a chlorine atom, which has the largest EA in the elements table . A large variety of superhalogens have been discovered experimentally or theoretically. In recent years, magnetic superatoms have attracted increasing research interests from the scientific community. The general strategy for designing magnetic superatoms is based on transition-metal atoms that have partially filled localized d orbitals . For example, superatoms VNa 8 and VNa 9 have been found to behave like single Mn and Cr atoms, respectively .…”
Section: Introductionmentioning
confidence: 99%